Detection of circulating anti-retinal antibodies in dogs with sudden acquired retinal degeneration syndrome using indirect immunofluorescence: A case-control study. (April 2020) - Mowat, Freya M.; Avelino, Janelle; Bowyer, Ashley; Parslow, Vanessa; Westermeyer, Hans D.; Foster, Melanie L.; Fogle, Jonathan E.; Bizikova, Petra
Abstract: Sudden acquired retinal degeneration syndrome (SARDS) in dogs is proposed to have an immune-mediated etiology. However, there is conflicting evidence regarding the presence of antiretinal antibodies, as assessed by western blotting, in the serum of SARDS patients. Because of the possibility that antibodies recognize only conformational epitopes, we hypothesized that a more sensitive method to investigate circulating retinal autoantibodies in SARDS is immunofluorescence. Sera from 14 dogs with early SARDS, and 14 age- and breed-matched healthy control dogs were screened for circulating antiretinal IgG, IgM, IgE and IgA using indirect immunofluorescence on lightly fixed frozen sections of normal canine retina. Controls without canine serum were also performed. A nuclear counterstain was used to identify cellular retinal layers. Images were obtained using a fluorescence microscope, and 2-3 separate masked observers graded retinal layers for fluorescence staining intensity using a 0–3 scale. Total circulating IgG and IgM was assessed by radial immunodiffusion. Statistical analysis was performed using 2-way ANOVA, paired 2-tailed student's t-test and correlation analysis. Intensity of IgG staining of photoreceptor outer segments was significantly higher using serum from dogs with SARDS compared with healthy controls in 2/3 observers ( P  < 0.05). Intensity of IgM staining throughout the retina was higher in SARDS dogs compared to matched healthy controls ( P  < 0.0001), although no specific retinal layer was statistically significant. There were no differences in staining intensity for IgE or IgA. Dogs with SARDS had a comparably lower circulating IgG and higher IgM than healthy controls ( P  = 0.01 and 0.001 respectively) and IgG and IgM were negatively correlated (r = −0.69, P  = 0.007). Despite having decreased serum IgG compared with healthy controls, circulating IgG in dogs with SARDS binds photoreceptor outer segments to a greater extent. Dogs with SARDS have a relatively higher circulating IgM than matched healthy controls. The pathogenic nature of these antibodies is unknown. Highlights: The serum of dogs with SARDS contains anti-photoreceptor IgG. Dogs with SARDS have elevated total circulating IgM and reduced total circulating IgG compared with matched controls. Canine SARDS and human AIR have similarities in terms of presence of antiretinal antibodies on indirect immunofluorescence.